A Life-Cycle Framework to Manage Collaboration and Knowledge Exchange in Open Organisations. (May 2022) - Guertler, M. R.; Adams, N.; Caldwell, G.; Donovan, J.; Hopf, A.; Roberts, J.
Abstract: Successful research and development requires interdisciplinary collaboration, often across organisational boundaries and for extended timeframes, such as in innovation networks or ecosystems. Open Organisation (OO) research can support collaboration and knowledge exchange in such situations. It builds on established concepts of Open Innovation through enhancing the exchange of knowledge by the exchange of humans. This paper contributes to OO research by presenting an OO lifecycle framework, which analyses evolving organisational and collaboration characteristics and resulting management needs.